Serum gamma-glutamyltranspeptidase distinguishes non-alcoholic fatty liver disease at high risk - (:unkn) unknown (H G E UPDATE MEDICAL PUBLISHING S A, 2008)
Background/Aims: Hepatocyte apoptosis is an important and invasive predictor of liver injury and fibrosis in non-alcoholic fatty liver disease (NAFLD). Increased gamma-glutamyltranspeptidase (GGT) level is frequently observed in NAFLD. Hepatocyte growth factor (HGF) Stimulates fibrogenesis and is correlated with GGT. The study aimed to determine whether GGT can distinguish NAFLD) patients at high risk. Methodology: Fifty biopsy-proven NAFLD patients (M/F: 24/26) were divided as the normal GGT group (n=255) and the high GGT group (n=25) (each patients' GGT > two fold of upper-limit of normal). Liver histology was graded according to Brunt et al. TNF-sRp55, caspase-3 and 8, NF kappa B and Bcl-2 were measured by immunohistochemical methods. For statistical analysis, Student's t test, chi-square test, multivariate regression analysis and the area under receiver operating characteristic (ROC) curve were used. Results: The high GGT group had significantly higher NF kappa B, caspase-3 and 8, and Bcl-2 levels (54.52 +/- 26.02 p=0.002; 55.95 +/- 27.18, p=0.002; 47.85 +/- 28.04, p=0.001; 11.19 +/- 12.33, p=0.016, respectively). Serum TNF-sRp55 levels of both groups were similar (29922.93 +/- 307.26, and 2885 +/- 194.47; p=0.79). Differences in reference to histological steatosis grade and inflammation were not significant. However, fibrosis stage was higher in the high GGT group (p=0.048). Conclusion: Multinominal logistic regression analysis showed that increased GGT level was a risk factor for advanced fibrosis in NAFLD (OR: 1.0, CI: 0.98-1.01; p=0.032). Using serum GGT levels the area under the ROC curve for the prediction of advanced fibrosis was 0.74 (95%CI: 0.54-0.94). The serum GGT cut-off value for the prediction of advanced fibrosis was 96.5U/L; with 83% sensitivity and 69% specificity.
Keywords: non-alcoholic fatty liver disease; gamma-glutamyltranspeptidase; hepatocyte apoptosis; fibrosis; HEPATITIS-C VIRUS; NF-KAPPA-B; BIOCHEMICAL MARKERS; ALCOHOLIC STEATOHEPATITIS; HEPATOCYTE APOPTOSIS; INJURY; ACTIVATION; EXPRESSION; FIBROSIS; RAT